Dexamethasone and granulocyte colony-stimulating factor alter the representation of cellular patterns and neurotisation of regenerative neuroma - O. M. Grabovyi; N. M. Nevmerzhytska; O. B. Alyokhin; H. B. Kostynskyi; H. Yu. Kondaurova (Patologìâ)
Aim. To evaluate the changes in the total cellularity (Nuc) of the rat sciatic nerve regenerative neuroma (RegN) and its representation of CD90, CD44, CD146, and CD133 positive cells, as well as its neurotization under the conditions of dexamethasone (Dex) and granulocyte colony-stimulating factor (GCSF).